2009
DOI: 10.1007/s10725-009-9374-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brassinosteroids on barley root growth, antioxidant system and cell division

Abstract: Homobrassinolide (HBR), which is one of the most biologically active forms of Brassinosteroids (BRs), was used to examine the potential effects of hormone on root germination, antioxidant system enzymes and cell division of barley (Hordeum vulgare L.). Seeds were germinated between filter papers in 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 30 publications
5
36
0
Order By: Relevance
“…In this respect JA dose not only antagonize the inhibiting action of the ethyl alcohol but slightly activates mitosis in most concentrations used. The mitodepressive effect of the hormones under study is in agreement with the effect of other hormones (Howell et al, 2007 andKartal et al, 2009). …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this respect JA dose not only antagonize the inhibiting action of the ethyl alcohol but slightly activates mitosis in most concentrations used. The mitodepressive effect of the hormones under study is in agreement with the effect of other hormones (Howell et al, 2007 andKartal et al, 2009). …”
Section: Resultssupporting
confidence: 87%
“…The micronuclei may be also resulted from lagging chromosome. Similar results were observed by the plant hormone homobrassinolide that induced a numbers of mitotic abnormalities in barley root (Kartal et al, 2009). …”
Section: Resultssupporting
confidence: 76%
“…BRs are found to affect the transcription and translation processes of specific genes related to stress tolerance (Bajguz 2000;Dhaubhadel et al 2002;Kagale et al 2007). Kartal et al (2009) reported that 28-HBL treatment significantly increased protein content in barley seedlings. Kulaeva et al (1991) reported that BRs can protect cereal leaf cells from heat shock stress.…”
Section: Discussionmentioning
confidence: 98%
“…They are highly effective in stimulating growth in young vegetative tissues. Brassinosteroids promoted elongation of mung bean, soybean, pea epicotyls, bean, sunflower and cucumber hypocotyls, Arabidopsis peduncles and Hordeum vulgare seedlings (Gregory, 1982;Clouse et al, 1992;Yu et al, 2004;Clouse, 2008 andKartal et al, 2009). Hypocotyl elongation of Packchoi (Brassica chinensis) by brassinosteroids was reported (Wang et al, 1993) and application to apical 3-mm region gave the best effect.…”
Section: Discussionmentioning
confidence: 98%